Simplex‐based adaptive parametric model order reduction for applications in optimization. (27th June 2017) - A. O. Leite, Mateus; Delinchant, Benoit; Guichon, Jean‐Michel; A. Vasconcelos, João
Abstract: A new methodology for optimization using parametric reduced order models is introduced. An adaptive scheme to place the expansion points in the reduction step is combined with a smart parametric space sampling in the optimization step to produce very reliable reduced order models. The methodology is illustrated in a demonstrative electromagnetic problem with appreciable gain in computational time. This technique is of general application and can be used to speed up optimization processes in many areas of engineering.